Stuart Hall Conversations, Projects and Legacies - Henriques, Julian; Morley, David (Goldsmiths Press, 2018)
Stuart Hall: Conversations, Projects and Legacies examines the career of the cultural studies pioneer, interrogating his influence and revealing lesser-known facets of his work. This collection of essays and photographs evaluates the legacies of his particular brand of cultural studies and demonstrates how other scholars and activists have utilised his thinking in their own research.